The Effect of Giving Endorphin Massage on the Level of Back Pain in Third Trimester Pregnant Women - Farida Barakati; Widia Shofa Ilmiah (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Several psychological and physical physiological changes take place in pregnant women during the third trimester. Complaints of back pain, which can cause discomfort during pregnancy, are one of the frequent physical changes that occur. Endorphin massage, a light massage approach that may help alleviate these complaints, is one strategy that may be utilized to promote relaxation and comfort for expectant mothers, particularly during the later stages of pregnancy before delivery. The purpose of this research is to assess the impact of endorphin massage on the severity of back discomfort in expectant women during their third trimester. The study used a quantitative methodology with a sample size of 65 participants that were representative of the study population. The Wilcoxon Signed Rank Test was used to compare pain ratings before and after the intervention. According to the test findings, there is a substantial difference between the two measurement outcomes, as evidenced by a value of Z = -8.062 with p = 0.000. The study's results indicate that every subject's pain was reduced after receiving endorphin massage. In conclusion, endorphin massage is beneficial for alleviating back pain in pregnant women during the third trimester.